2022
DOI: 10.1002/rth2.12670
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic emicizumab for hemophilia A in the Asia‐Pacific region: A randomized study (HAVEN 5)

Abstract: Background Emicizumab is a subcutaneously administered humanized, bispecific, monoclonal antibody approved for prophylaxis in people with hemophilia A. Methods HAVEN 5 (NCT03315455) is a randomized, open‐label, phase 3 study of individuals aged ≥12 years with severe hemophilia A without factor VIII (FVIII) inhibitors, or hemophilia A of any severity with FVIII inhibitors, across the Asia‐Pacific region. Participants were randomly assigned (2:2:1) to receive emicizumab 1.5 mg/kg once weekly (arm A), emicizumab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 31 publications
4
38
1
1
Order By: Relevance
“…6,7 Emicizumab can be administered subcutaneously, and it has a long plasma half-life of approximately 30 days, making regimens of once every 1-4 weeks possible. [8][9][10][11][12][13][14][15] Emicizumab has improved procoagulant potential in patients with severe HA to subnormal or mild HA patients, 16,17 irrespective of the presence of FVIII inhibitors. 4 The effectiveness of emicizumab in preventing repeated bleeding has been confirmed by global clinical phase 3(HAVEN 1-5 [10][11][12][13][14] and HOHOEMI studies 15 ) and real-world data for patients with HA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Emicizumab can be administered subcutaneously, and it has a long plasma half-life of approximately 30 days, making regimens of once every 1-4 weeks possible. [8][9][10][11][12][13][14][15] Emicizumab has improved procoagulant potential in patients with severe HA to subnormal or mild HA patients, 16,17 irrespective of the presence of FVIII inhibitors. 4 The effectiveness of emicizumab in preventing repeated bleeding has been confirmed by global clinical phase 3(HAVEN 1-5 [10][11][12][13][14] and HOHOEMI studies 15 ) and real-world data for patients with HA.…”
Section: Introductionmentioning
confidence: 99%
“…This humanized bispecific monoclonal antibody (mAb) mimics the cofactor function of activated FVIII by spatially relocating FIXa/FIX and FX/FXa to the appropriate position in the tenase assembly 6,7 . Emicizumab can be administered subcutaneously, and it has a long plasma half‐life of approximately 30 days, making regimens of once every 1–4 weeks possible 8–15 . Emicizumab has improved procoagulant potential in patients with severe HA to subnormal or mild HA patients, 16,17 irrespective of the presence of FVIII inhibitors 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Standard‐dose FVIII replacement therapy in non‐inhibitor patients receiving emicizumab prophylaxis is recommended for severe breakthrough bleeds or surgical intervention 14–16,33 . The additive effect of FVIII in the presence of emicizumab was reported under in vitro conditions, 38,39 potentially reflecting no thrombosis with concomitant use.…”
Section: Bispecific Antibodymentioning
confidence: 99%
“…The efficacy, safety, and pharmaceutics of these treatments have been further studied in the phase 3 HAVEN 3-5 studies, which included adults/adolescents ≥ 12 years of age with and without inhibitors ( 100 102 ). These trials demonstrated that emicizumab prophylaxis achieved remarkable efficacy for bleeding control and was well tolerated in HA patients, regardless of FVIII inhibitor status.…”
Section: Novel Strategies For Treating Ha With Inhibitorsmentioning
confidence: 99%
“…Moreover, 0.33% (25/7500) of subjects produced an immune response to emicizumab ( 93 ). In the HAVEN trials, 2 out of 88 pediatric participants in HAVEN 2 ( 99 , 105 ) and 1 out of 64 evaluable participants in HAVEN 5 ( 102 ) developed anti-drug antibodies (ADAs) with neutralizing potential. Although this occurs infrequently, it is necessary to monitor the neutralizing ADAs to implement immunological surveillance in HA patients with emicizumab regimens.…”
Section: Novel Strategies For Treating Ha With Inhibitorsmentioning
confidence: 99%